Also Innovators How one computer salesman contributed to the digital revolution - Yardley, Christopher B. (ANU Press, 2019)
'Thank you for your order, Mr Mainframe Customer. The cost is £5 million and the lead-time for manufacture will be two years. In the meantime you will have to build a special computer centre to our specification. For our part, our project team will help you recruit and train potential programmers and we shall advise on how you might use the system.' How different from today when the customer will want to see a specific application running before he puts a hand in his/her pocket. Chris Yardley lived the changes as a computer salesman and tells his story of a career living and working in five countries. Warts and all. The ecstasies, the heartbreaks and idiocies of major corporations. His career was not a planned one. In a growing industry, opportunities presented themselves and Chris believes he grasped every one presented. Having written his story, he has had every chapter verified by at least one person who features in that narrative. His respondents have universally endorsed the facts with comments such as 'Wow, I'd forgotten most of that'. 'You have a fantastic memory.' 'I never knew before the full facts of what happened.' 'How have you remembered all the circumstances?' 'It really is a people business.' His career was not a planned one. In a growing industry, opportunities presented themselves and Chris believes he grasped every one presented. Having written his story, he has had every chapter verified by at least one person who features in that narrative. His respondents have universally endorsed the facts with comments such as 'Wow, I'd forgotten most of that'. 'You have a fantastic memory.' 'I never knew before the full facts of what happened.' 'How have you remembered all the circumstances?' 'It really is a people business.'